Peranan Kepala Desa Dalam Pelaksanaan Pembangunan Ditinjau Dari Fiqh Siyasah dan UU Desa No. 6 Tahun 2014 - Mirza Rahmatillah; Ridwan Nurdin (Law Department, Sharia and Law Faculty., 2020)
The success of developing a village cannot be separated from the role of the Village Head and the entire community. A developed village can be seen from the adequate facilities and infrastructure. The head of government has a big responsibility for the progress of his village in order to create a prosperous society. The formulation of the problem in this study is how the role of the village head in the implementation of development in Li-Eue Village and how the Siyasah Fiqh and Village Law review the role of the village head in the implementation of development in Li-Eue Village. This type of research is classified as field research (field research), which is descriptive analysis, namely research that tells and describes data sourced from primary data through interviews, observations and reports in the form of documents and secondary data by conducting library research in the form of Al- Qur'an, Hadiths, opinions of scholars, laws and regulations, documents and books and other scientific works. Based on the results of the analysis, it can be concluded that the role of the Li-Eue Village head in the implementation of development in Li-Eue Village is generally less than optimal so that it is less trustworthy or responsible for the duties as village head. Judging from the existence of several developments that have not been implemented. And less transparent and less mobilizing community participation. Review of Siyasah Fiqh and Village Law, namely leaders who are less trustworthy and less responsible.